“There are support resources, but they are kind of hidden”: social network analysis of college students' support systems in relation to type 1 diabetes management - Malova, Ekaterina (Frontiers in Human Dynamics, 2024)
Type 1 diabetes is an invisible disability requiring major life changes and constant monitoring. It can become particularly challenging to control during a major life transition. This study examines the composition and nature of the social networks of college students living with type 1 diabetes. A total of 17 respondents with type 1 diabetes and 18-25 years of age participated in network interviews. Network Canvas facilitated online data collection. The results show that efforts to protect the well-being of college students with T1D require active participation of university organizations and certain individuals from students' formal and informal connections. Such connections define students' support networks in college and provide access to social capital.Practical implications and recommendations for university leadership and students' parents are discussed.